Effect of antioxidant active films on the oxidation of soybean oil monitored by Fourier Transform Infrared Spectroscopy - Anbinder, Pablo Sebastián (2015)
An active film prepared from waterborne polyurethane incorporated with different concentrations of butylated hydroxytoluene (BHT) and α-tocopherol was developed, and the films? antioxidant characteristics were studied using soybean oil as food model. The release behavior of additives from such films was studied using isooctane as a simulant fatty food. Antioxidant activity of the films into soybean oil at three experimental conditions was monitored by FTIR spectroscopy. Induction time and the kinetics of the oxidation process were followed using different bands of the FT-IR spectra. Films incorporated with 2 wt.% of BHT or α-tocopherol showed enough antioxidant activity to preclude oil oxidation during 60 days at 60 °C in the dark. The results showed that this type of active films could be used for food preservation as part of a packaging containing oils or oily related products.